ACCOUNTING AUDIT PROFESSION IN DIGITAL TRANSFORMATION ENVIRONMENT BETWEEN THEORETICAL FRAMEWORK AND PRACTICAL REALITY 2023 (World Economics and Finance Bulletin, 2023)
Digital transformation (DT) has become the most important requirement of the working environment in enterprises because of its importance and its significant role in all occupations, especially the profession of accounting auditing through its technological and advantages despite risks and constraints . The accounting profession, like any, must be flexible, evolve, adapt to technological evolution and embrace DT. Whatever the technological development, DT and other nature and mechanism of providing audit services, the main objective of this profession will remain the need for owners of enterprises (especially Joint Stock Companies) to have a professional opinion independent of the management's adequacy in using its available resources and achieving sustainability. The study concluded that emphasis should be placed on training and developing the skills of employees in the field of auditing accounts on an ongoing basis and familiarizing them with all developments in the modern business and technological world environment, digitization and all factors affecting clients' financial centres or the sustainability of their resources and the continuation of their businesses . In addition to developing and activating the professional organization of the accounting and auditing profession in line with the requirements of both rational corporate movement and thoughtful DT; In addition to updating the Charter of Professional Conduct to which the certified accountant and auditor must adhere under the cloud computing environment, electronic auditing and all modern forms of DT. It should be preceded by a very important step: regulating a legislative and legal environment that regulates work in the new digital business environment and sets standards for digital accounting work.
Keywords: digitization; accounting; auditing; digital transformation